The South China Sea arbitration a Chinese perspective - Talmon, Stefan 1965-; Jia, Bing-Bing 1966- (Hart Publishing, 2014)
The book aims to offer a Chinese perspective on some of the issues raised in the arbitral proceedings of the South China Sea dispute between the Republic of the Philippines and the Peoples Republic of China.
Keywords: Conference on the Law of the Sea; Arbitration (International law); Jurisdiction (International law); Maritime boundaries -- China; South China Sea -- International status; United Nations Convention on the Law of the Sea -- (1982); Grenzkonflikt; Philippinen; Südchinesisches Meer; China